Modelling and scheduling of transportable energy storage systems using a time space network technique - Seah, Zuo Hang (Nanyang Technological University, 2021)
Large area blackouts lead to widespread catastrophic consequences for economy and society. It highlights the importance of power systems resilience against major disruptions, especially for distribution systems (DSs). In a more resilient DS, electric service restoration can be implemented efficiently using stationary and transportable sources. Equipped with vehicles, transportable sources, such as transportable energy storage systems (TESSs), have great potential to enhance the resilience through optimal scheduling among multiple islands within the DS. The scheduling of TESSs and network reconfiguration of DSs should be jointly optimized in the post-disaster restoration. After a disaster, there exists multiple faults in the DS, and the network reconfiguration is necessary to improve the resilience via forming multiple islands, while TESSs can affect the power balance in each island through a sequence of trips (e.g., an optimal scheduling of TESSs).